Dual-neutrality for the Koreas: a two-pronged approach toward reunification. Issue 3 (3rd July 2022) - Lottaz, Pascal; Gärtner, Heinz
ABSTRACT: This article builds a novel argument for the unification of the two Korean states by way of a dual neutralisation process. After reviewing the neutralisation concept and the history of neutrality ideas for the peninsula, the authors introduce two historical models that would fit the security needs of both Koreas and their respective security partners. Using a realist framework, it is argued that the "Finlandisation" of the DPRK on the one hand; and the "Austriasation" of the ROK on the other, would not change the de facto security relationships with their patrons, but would create the structural underpinning for future foreign policy compatibility. Assuming other factors remain equal and a solution to internal political division could be brokered, the article proposes a security framework for both states aimed at separately creating the structures for a future unified neutral Korea.